Pengaruh Pengetahuan Ibu dalam Mempengaruhi Motivasi Pemberian ASI Eksklusif di Kelurahan Talang, Kecamatan Bayat, Kabupaten Klaten - Ayu Nurkhayati (Jurnal Multidisiplin Madani, 2022)
The study aims to determine the relationship between mother's knowledge about Exclusive Breastfeeding with Exclusive Breastfeeding motivation. The study uses quantitative method with the proposed hypothesis that there is a positive relationship between mother's knowledge about Exclusive Breastfeeding with Exclusive Breastfeeding motivation. The subjects in this study are mothers who have toddlers (babies under five years old) in Talang Village, Bayat District, Klaten Regency, totaling 58 subjects. The method of collection data uses a mother's knowledge scale about Exclusive Breastfeeding with motivation scale for Exclusive Breastfeeding. The writer uses the Kendall's Tau correlation technique to analyze the data. Based on the results of Kendall's Tau analysis, the correlation coefficient (r) is 0.868; p = 0.000 (p < 0.01) means that there is a very significant positive relationship between mother's knowledge about Exclusive Breastfeeding with Exclusive Breastfeeding motivation. The effective contribution between the variables of mother's knowledge about Exclusive Breastfeeding with Exclusive Breastfeeding motivation is 83.8%. Based on the results of the analysis, it is known that the variable mother's knowledge about Exclusive Breastfeeding has an empirical mean (RE) of 13.10 and a hypothetical mean (RH) of 8, which means that mother's knowledge about Exclusive Breastfeeding is moderate. The variable of Exclusive Breastfeeding motivation is known to be an empirical mean (RE) of 55.70 and a hypothetical mean (RH) of 45, which means that Exclusive Breastfeeding motivation to the subject is classified as moderate. The conclusion obtained from the study is that there is a very significant positive relationship between mother's knowledge about Exclusive Breastfeeding with Exclusive Breastfeeding motivation.